Investigating Indonesian Spelling Error on the Learners’ Composition - Dwi Dian Panike; Kasmantoni Kasmantoni; Randi Randi (Jadila: Journal of Development and Innovation in Language and Literature Education, 2022)
The aim of this research was to investigate errors in the implementation of EBI (Indonesian Spelling System) on the learners’ composition of the second grade students of SMAN 05 Kepahiang. In order to analyze the case deeply and comprehensively, this research was designed by using qualitative approach and content analysis method with data gathering techniques in the form of documentation. The data of this research were collected through purposive sampling and analyzed by using an interactive model consisting of four stages: data collection, data reduction, data presentation, and withdrawal conclusion. The result of this research revealed that the learners’ errors in the implementation of EBI on their composition included misusing of capital letters, italics, prepositions, commas, and compound words. In academic writing, the errors need to be avoided as such errors can interfere with the effectiveness and efficiency of the learners’ composition in Indonesian.